Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/acel.13488
|View full text |Cite
|
Sign up to set email alerts
|

Metformin treatment of diverse Caenorhabditis species reveals the importance of genetic background in longevity and healthspan extension outcomes

Abstract: Metformin, the most commonly prescribed anti‐diabetes medication, has multiple reported health benefits, including lowering the risks of cardiovascular disease and cancer, improving cognitive function with age, extending survival in diabetic patients, and, in several animal models, promoting youthful physiology and lifespan. Due to its longevity and health effects, metformin is now the focus of the first proposed clinical trial of an anti‐aging drug—the Targeting Aging with Metformin (TAME) program. Genetic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 49 publications
3
36
0
Order By: Relevance
“…The anti-diabetic drug metformin has many effects on metabolism, including stimulating AMPK indirectly (56). It may be consistent with our results that metformin not only extends C. elegans lifespan but also delays the decline in swimming capacity with aging (57).…”
Section: Discussionsupporting
confidence: 90%
“…The anti-diabetic drug metformin has many effects on metabolism, including stimulating AMPK indirectly (56). It may be consistent with our results that metformin not only extends C. elegans lifespan but also delays the decline in swimming capacity with aging (57).…”
Section: Discussionsupporting
confidence: 90%
“…We also tested metformin, the biguanide diabetes drug that has been reported to increase lifespan in a range of organisms, including C. elegans ; 43 a recent study confirmed that metformin has lifespan and healthspan benefits for several (but not all) Caenorhabditis species. 44 A previous study had concluded that metformin's effects on C. elegans lifespan are mediated by perturbation of bacterial folate cycle metabolism, resulting in methionine restriction, rather than through metformin's effects on the worm itself. 45 However, those and prior assays were performed with very high (25–100 mM) levels of metformin in the plates.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we tested whether non-genetic means of promoting health could also induce changes to sleep in WT animals. Administering low doses of mitochondria-targeted agents, such as Rotenone and Metformin, can improve health and extend lifespan by eliciting hormetic responses (De Haes et al, 2014;Martin-Montalvo et al, 2013;Na et al, 2015;Na et al, 2013;Onken et al, 2022;Schmeisser et al, 2013;Yuyun et al, 2013). Therefore, we examined sleep in WT flies that were fed 0.1 µM of Rotenone or 5 mM of Metformin, which are the optimal doses required for improved health span (Na et al, 2015;Schmeisser et al, 2013).…”
Section: Improved Health Correlates With Reduced Sleepmentioning
confidence: 99%